Prisoners of the past [videorecording] - Dormer, Mike.; Fairley, John.; Hughes, Gruyneth; Marshall, Jill.; Welfare, Simon ([S.l.] Granite Production for Yorkshire Television, 1990)
Covers the communist leadership of Breznew, Andropov and Konstantin Chernenko and Michael Gorbachev. Also deals on the KGB KOMSOMOL of the Communist Party of the Soviet Union.
VHS.
Credits : Narrator Sian Phillips ; Editors, Maggie Knox, Martin Roche.
Keywords: Communist leadership -- Russia; Russia -- Politics and government -- 1945-1991.; Russia -- Social conditions -- 1945-1991.